Kepemimpinan Kepala Sekolah Dalam Perspektif Psikologi Islam: Strategi Meningkatkan Mutu Pendidikan Dan Mewujudkan Sekolah Berkarakter - Muchlisin, Imam (Indonesia, 2022)
Education is a fundamental need that cannot be separated from efforts to educate the nation and form skilled individuals in their fields. School principals play a crucial role in improving the quality of education, with the quality of the principal's leadership greatly influencing various aspects of school life. In an Islamic psychology perspective, school principal leadership does not only focus on managing resources, but also on implementing spiritual and moral principles that can strengthen the quality of education. This article discusses the leadership strategies of school principals from an Islamic psychology perspective, highlighting the importance of good management in achieving the vision and mission of education. Effective leadership not only improves the quality of education but also supports the development of student character, which in turn contributes to the realization of schools of excellence and character. Character education, as an integral part of the educational process, seeks to direct individual development towards a better civilization, reflecting values ​​and principles that are in harmony with Islamic psychology.